2019
DOI: 10.1002/advs.201902508
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Nondoped Blue Delayed Fluorescence Organic Light‐Emitting Diodes Featuring Low Driving Voltage and High Brightness

Abstract: TADF) materials without using heavy metals have gained great attention as the third-generation organic light-emitting diode (OLED) emitters. [8][9][10][11][12][13][14][15][16][17][18][19][20] The use of pure organic TADF emitters allows almost 100% internal electroluminescence (EL) quantum efficiency by harvesting the triplet excitons (T 1 ) to the emissive singlet excited states (S 1 ) via reverse intersystem crossing (RISC). To date, high external quantum efficiency (EQE) exceeding 20% has been achieved for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…To reduce ΔE 3LE-de,3CT , one strategy is to lower the 3 LE energy with a secondary donor. [11,14] However, this leads to the redshifted emission. Another strategy is to increase the CT energy to approach the high-lying 3 LE by reducing the number of Cz moieties, though this negates the advantages of the multiple Ds motif and thus correspondingly leads to reduced k RISC s though a blueshifted emission.…”
Section: Doi: 101002/adma201908355mentioning
confidence: 99%
“…To reduce ΔE 3LE-de,3CT , one strategy is to lower the 3 LE energy with a secondary donor. [11,14] However, this leads to the redshifted emission. Another strategy is to increase the CT energy to approach the high-lying 3 LE by reducing the number of Cz moieties, though this negates the advantages of the multiple Ds motif and thus correspondingly leads to reduced k RISC s though a blueshifted emission.…”
Section: Doi: 101002/adma201908355mentioning
confidence: 99%
“…As a result, the 13-based fully solution-processed blue OLED realizes a maximum EQE of 22.6%, which is almost 20 times higher than that of the 14-based OLED. With the same emission core, Tang et al 59 also reported two 4CzBN-based blue TADF emitters 15 and 16 by introducing steric groups. Both emitters exhibit blue emission at 464 nm with a CIE y < 0.2 and an EQE over 20% in doped devices.…”
Section: Tadf Emitters For Nondoped Oledsmentioning
confidence: 99%
“…Consequently, those materials possess larger bandgaps and thus devices based on them typically require higher drive voltages than those using fluorescent emitters. (Note that there is increasing research on using nondoped phosphorescent [ 131 ] and TADF emitters, [ 132,133 ] which may reduce drive voltages compared to host–guest systems. [ 133 ] ) Low drive voltages are important for biomedical applications, not only for reducing power consumption and for integration with electronic drivers, but also for reducing resistive heating of the environment.…”
Section: Oled Requirements For Biomedical Applicationsmentioning
confidence: 99%
“…(Note that there is increasing research on using nondoped phosphorescent [ 131 ] and TADF emitters, [ 132,133 ] which may reduce drive voltages compared to host–guest systems. [ 133 ] ) Low drive voltages are important for biomedical applications, not only for reducing power consumption and for integration with electronic drivers, but also for reducing resistive heating of the environment. Especially applications involving direct contact of the light source with live cells and in particular brain tissue need to retain the environment at physiological temperatures, which means that only a temperature increase up to around 1 °C is tolerated.…”
Section: Oled Requirements For Biomedical Applicationsmentioning
confidence: 99%